Composite material and preparation method thereof, light-emitting device and display device

Through the method of alkaline treatment and mixing with an olefin clustering by Pedot: PSS, the problem of poor stability of the PEDOT: PSS thin film interface, and realized the efficient light emitting and mechanical flexibility of the luminous device.

CN119371782APending Publication Date: 2025-01-28TCL TECHNOLOGY GROUP CORPORATION +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310928883.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-07-26
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

During the long-term electrical stimulation process, the existing PEDOT:PSS film has poor interface stability, which causes the film to expand and contract, produce cracks and fall off, affect hole transmission, and reduce the luminous efficiency of the light-emitting device.

Method used

By performing alkaline treatment of PEDOT: PSS, part of the shed PSS and olefin co -vector mixes to form composite materials, embedded between PEDOT and PSS to promote the doping of olefin sync, and prevent Pedot's water absorption.

Benefits of technology

Improving the problem of film defects formed by composite materials, improved the luminous efficiency of the luminous devices, and enhanced the hydrophobic performance and mechanical flexibility of the PEDOT film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371782A_ABST
    Figure CN119371782A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material and a preparation method thereof, a light-emitting device and a display device, and relates to the technical field of display. The preparation method comprises the following steps: providing PEDOT: PSS and an olefin copolymer, carrying out alkaline treatment on the PEDOT: PSS to obtain a composite material precursor solution, and the composite material precursor solution comprises PEDOT: PSS with a PSS part falling off; and mixing the olefin copolymer with the composite material precursor solution to obtain the composite material. According to the method, PEDOT: PSS is placed in an alkaline environment, so that part of PSS in the same molecule is effectively separated from PEDOT, an olefin copolymer is embedded between PEDOT and PSS, water absorption swelling of PEDOT is prevented, alkaline treatment is beneficial to improvement of the yield of PEDOT: PSS with PSS part falling off, doping of the olefin copolymer is promoted, the yield of the composite material is improved, and the defect of a film formed by the composite material is overcome.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of display technology, and in particular to a composite material and a preparation method thereof, a light-emitting device, and a display apparatus. Background Art

[0002] The light-emitting devices widely used at present are organic light-emitting diodes (OLEDs) and quantum dot light-emitting diodes (QLEDs). The structure of traditional OLED and QLED devices generally includes an anode, a hole functional layer, a light-emitting layer, an electron functional layer and a cathode. Under the action of the electric field, the holes generated by the anode of the light-emitting diode and the electrons generated by the cathode move and are injected into the hole functional layer and the electron functional layer respectively, and finally migrate to the light-emitting layer. When the two meet in the light-emitting layer, energy excitons are generated, thereby exciting the light-emitting molecules and finally producing visible light.

[0003] Poly (3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS) is a conductive polymer aqueous dispersion and is widely used as a hole functional material for light-emitting devices. PEDOT:PSS is composed of PEDOT and PSS. PEDOT is a polymer of EDOT (3,4-ethylenedioxythiophene monomer) and PSS is polystyrene sulfonate. PSS can significantly improve the solubility of PEDOT. PEDOT:PSS film has the advantages of good mechanical properties, thermal stability, processability, high transparency and low cost, which makes it applicable to many different fields such as antistatic coatings, electronic conductive coatings, thermoelectric materials, supercapacitors, organic light-emitting diodes, organic thin film transistors, organic solar cells, etc.

[0004] However, when PEDOT:PSS is used in light-emitting devices, the interface stability between the PEDOT:PSS film and the electrode is poor. During long-term electrical stimulation, the volume of the PEDOT:PSS film will expand and contract, causing cracks at the interface between the PEDOT:PSS film and the electrode, and even causing the PEDOT:PSS film to fall off, affecting the transmission of holes and thus resulting in low luminescence efficiency of the light-emitting device. Summary of the invention

[0005] In view of this, the present application provides a method for preparing a composite material, aiming to improve the problem of defects in the existing PEDOT:PSS film.

[0006] The embodiment of the present application is implemented as follows: a method for preparing a composite material, comprising:

[0007] Provide PEDOT:PSS and olefin copolymers;

[0008] treating the PEDOT:PSS with alkaline to obtain a composite material precursor solution, wherein the composite material precursor solution includes PEDOT:PSS with PSS partially detached;

[0009] The olefin copolymer is mixed with the composite material precursor solution to obtain the composite material.

[0010] Optionally, in some embodiments of the present application, the alkaline treatment of the PEDOT:PSS comprises:

[0011] The PEDOT:PSS is dissolved in a first solvent to obtain a PEDOT:PSS solution; and the PEDOT:PSS solution is mixed with an alkaline solution to obtain the composite material precursor solution.

[0012] Optionally, in some embodiments of the present application, in the PEDOT:PSS solution, the concentration of PEDOT:PSS is 30 mg / mL to 50 mg / mL; and / or

[0013] The molar concentration of the alkaline solution is 0.01 mol / L to 0.2 mol / L; and / or

[0014] The pH of the composite material precursor solution is 8 to 12; and / or

[0015] The alkaline solution includes one or more of KOH, NaOH, LiOH, Cs(OH)2, Ba(OH)2, NH3, and tetramethylammonium hydroxide; and / or

[0016] The first solvent includes one or more of water and dimethyl sulfoxide; and / or

[0017] The solvent in the alkaline solution includes water.

[0018] Optionally, in some embodiments of the present application, after mixing the PEDOT:PSS solution with the alkaline solution, ultrasonic treatment is further performed; and / or

[0019] After the PEDOT:PSS solution is mixed with the alkaline solution, a precipitant is added, the alkaline solution is separated and removed, and a second solvent is added to obtain a composite material precursor solution.

[0020] Optionally, in some embodiments of the present application, the frequency of the ultrasonic treatment is 25kHz to 40kHz; and / or

[0021] The ultrasonic treatment time is 10min to 240min; and / or

[0022] The precipitant comprises one or more of ethanol, butanol and pentanol; and / or

[0023] The second solvent includes one or more of water and dimethyl sulfoxide; and / or

[0024] The mass ratio of the PEDOT:PSS solution to the precipitant is 1:4.

[0025] Optionally, in some embodiments of the present application, in the PEDOT:PSS, the mass ratio of PEDOT to PSS is 1:(8-15); and / or

[0026] In the composite material precursor solution, the concentration of PEDOT:PSS is 30 mg / mL to 50 mg / mL; and / or

[0027] The mass ratio of the PEDOT:PSS to the olefin copolymer is 1:(0.001-0.1); and / or

[0028] The olefin copolymer includes one or more of polyvinyl alcohol, poly(ethylene-vinyl acetate), polyvinyl acetate, and styrene block copolymer; and / or

[0029] The olefin copolymer and the composite material precursor solution are mixed for 10 minutes to 24 hours; and / or

[0030] The temperature for mixing the olefin copolymer and the composite material precursor solution is 40° C. to 80° C.

[0031] Correspondingly, an embodiment of the present application further provides a composite material, which is prepared by the above-mentioned preparation method, and the composite material includes a composite of the olefin copolymer doped with PEDOT:PSS.

[0032] Correspondingly, an embodiment of the present application further provides a light-emitting device, comprising a stacked anode, a hole functional layer, a light-emitting layer and a cathode, wherein the material of the hole functional layer comprises the composite material prepared by the above-mentioned preparation method.

[0033] Optionally, in some embodiments of the present application, the thickness of the anode is 80nm to 100nm; and / or

[0034] The thickness of the hole functional layer is 3nm to 70nm; and / or

[0035] The thickness of the light-emitting layer is 20nm to 60nm; and / or

[0036] The thickness of the cathode is 40nm to 80nm; and / or

[0037] The materials of the anode and the cathode independently include one or more of metal, carbon material and metal oxide; the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes a metal oxide electrode or a composite electrode with a metal sandwiched between doped or undoped transparent metal oxides, the material of the metal oxide electrode includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, and the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or

[0038] The material of the light-emitting layer includes 4,4'-bis(N-carbazole)-1,1'-biphenyl: tris[2-(p-tolyl)pyridine iridium(III)], 4,4',4"-tris(carbazole-9-yl)triphenylamine: tris[2-(p-tolyl)pyridine iridium], diarylanthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, TADF materials, polymers containing BN covalent bonds, HLCT materials, Exciplex luminescent materials, CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, Cd ZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe, SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSe S, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs , GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, G aInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb, CuInS2, CuInSe2, AgInS2, CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZ One or more of nSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS, InP / ZnSe / ZnS, AMX3 and BMX3, where A is Cs+ ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion selected from Cl - Br - ,I - One or more of; B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n ≥ 2; and / or

[0039] The light-emitting device also includes an electronic functional layer arranged between the light-emitting layer and the cathode, the electronic functional layer includes one or more of an electron injection layer or an electron transport layer, the materials of the electron injection layer and the electron transport layer independently include one or more of doped or undoped inorganic particles, quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds, the inorganic particles include one or more of zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc selenide, indium phosphide, gallium phosphide, and barium titanate, and the doped elements include one or more of indium, gallium, aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium.

[0040] Optionally, in some embodiments of the present application, the hole functional layer includes a hole injection layer or a hole transport layer, and the material of the hole injection layer or the hole transport layer is a composite material obtained by the above preparation method; or

[0041] The hole functional layer includes a hole injection layer and a hole transport layer, one of the hole injection layer and the hole transport layer is a composite material obtained by the above-mentioned preparation method, and the material of the other layer of the hole injection layer and the hole transport layer includes the composite material obtained by the above-mentioned preparation method, 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-di(4-(N,N'-diphenyl-amino)- ) phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(carbazol-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent materials, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-) Phenyl vinylene, poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amine, polynuclear aromatic tertiary amine, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives , N,N'-di(naphthalene-1-yl)-N,N'-diphenylbenzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose and tetracyanoquinodimethane, doped graphene, undoped graphene, transition metal oxides, transition metal sulfides, transition metal tin compounds, doped or undoped zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc selenide, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, barium titanate, quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds. One or more of the following.

[0042] Correspondingly, the present application also provides a display device, which includes the above-mentioned light-emitting device.

[0043] The preparation method of the composite material provided in the present application first places PEDOT:PSS in an alkaline environment to obtain partially detached PEDOT:PSS, and then adds an olefin copolymer to embed it between PEDOT and PSS, thereby promoting the doping of the olefin copolymer and preventing PEDOT from absorbing water and swelling. The preparation method of the composite material improves the problem of thin film defects formed by the composite material, thereby improving the luminous efficiency of the light-emitting device. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0045] Figure 1 is a flow chart of a method for preparing a composite material provided in an embodiment of the present application;

[0046] Figure 2 is a schematic structural diagram of a light-emitting device provided in an embodiment of the present application;

[0047] Figure 3 This is an AFM image of the hole injection film provided in Example 1 of the present application.

[0048] Reference numerals:

[0049] Anode 10; hole functional layer 20; light emitting layer 30; cathode 40; electron functional layer 50. DETAILED DESCRIPTION

[0050] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0051] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.

[0052] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0053] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or several", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0054] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0055] The technical solution of this application is as follows:

[0056] See also Figure 1 The present application provides a method for preparing a composite material, comprising:

[0057] S11, providing poly (3,4-ethylenedioxythiophene):polystyrene sulfonate) (PEDOT:PSS) and an olefin copolymer;

[0058] S12, treating the PEDOT:PSS with alkalinity to obtain a composite material precursor solution, wherein the composite material precursor solution includes PEDOT:PSS from which the PSS is partially detached;

[0059] S13, mixing the olefin copolymer with the composite material precursor solution to obtain the composite material.

[0060] It should be noted that in PEDOT:PSS, PEDOT is the conductive part and PSS is the dispersed long chain. PEDOT and PSS are connected together by electrostatic binding force. In an alkaline environment, for PEDOT:PSS in the same molecule, part of the PSS will detach from PEDOT, while the other part will remain connected to PEDOT. The olefin copolymer can be embedded between the detached PSS and PEDOT molecules, and combined with PEDOT to form a composite of olefin copolymer doped PEDOT:PSS.

[0061] It can be understood that for PEDOT:PSS in the same molecule, there are multiple connection sites between PEDOT and PSS. After alkaline treatment, some of the connection sites are disconnected, that is, some PSS is separated from PEDOT, resulting in a gap, and the olefin copolymer is connected to PEDOT to fill the gap. In addition, during the alkaline treatment process, there may be partial unreaction or complete reaction, and a trace amount of PEDOT:PSS is unreacted, so that PSS does not fall off; and a trace amount of PEDOT:PSS over-reacts, so that for the same molecule, PSS is completely detached, thereby generating a trace amount of PEDOT that is not bound to PSS and PSS that is not bound to PEDOT.

[0062] The preparation method of the composite material provided by the present application is to first place PEDOT:PSS in an alkaline environment, effectively separate part of PSS from PEDOT under alkaline conditions, and then add olefin copolymer for doping. Olefin copolymer has the advantages of low modulus, high stretchability, high interfacial adhesion, etc., and contains a strong conjugated structure, which can form a strong dipole. Olefin copolymer is combined with PEDOT to construct an elastic polymer network to prepare a composite conductive material of an interpenetrating network of PEDOT and olefin copolymer. Olefin copolymer is embedded between PEDOT and PSS. Due to its large steric hindrance, PEDOT and PSS can be further separated, effectively preventing PEDOT from absorbing water and swelling, and improving the hydrophobic properties of PEDOT film, thereby realizing the formation of a tough conformal interface between PEDOT film and rigid electrode substrate, and improving the mechanical flexibility, high conductivity and long-term electrochemical stability of the light-emitting device.

[0063] In S12:

[0064] In some embodiments, in the PEDOT:PSS, the mass ratio of PEDOT to PSS is 1:(8-15), for example, 1:(9.5-14.5), 1:(10-14), 1:(10.5-13.5), 1:(11-13), 1:(11.5-12), etc. Within the mass ratio range, the conductivity and solubility of PEDOT:PSS are good.

[0065] In some embodiments, the alkaline treatment of the PEDOT:PSS comprises:

[0066] The PEDOT:PSS is dissolved in a first solvent to obtain a PEDOT:PSS solution; and the PEDOT:PSS solution is mixed with an alkaline solution to obtain a composite material precursor solution.

[0067] In some embodiments, the first solvent includes one or more of water and dimethyl sulfoxide.

[0068] In some embodiments, in the PEDOT:PSS solution, the concentration of PEDOT:PSS is 30 mg / mL to 50 mg / mL, for example, 32 mg / mL to 48 mg / mL, 34 mg / mL to 46 mg / mL, 36 mg / mL to 45 mg / mL, 38 mg / mL to 44 mg / mL, 40 mg / mL to 42 mg / mL, etc. Within the concentration range, spin coating is helpful to improve the quality of the film.

[0069] In some embodiments, the solute in the alkaline solution includes one or more of KOH, NaOH, LiOH, Cs(OH)2, Ba(OH)2, NH3, and tetramethylammonium hydroxide (TMAH).

[0070] In some embodiments, the solvent in the alkaline solution includes water.

[0071] In some embodiments, the molar concentration of the alkaline solution is 0.01 mol / L to 0.2 mol / L, for example, 0.02 mol / L to 0.18 mol / L, 0.04 mol / L to 0.16 mol / L, 0.05 mol / L to 0.15 mol / L, 0.06 mol / L to 0.12 mol / L, 0.08 mol / L to 0.1 mol / L, etc. Within the molar concentration range, after treatment with the alkaline solution, PEDOT and PSS are more easily separated without destroying the molecular structure of PEDOT.

[0072] In some embodiments, after mixing the PEDOT:PSS solution with the alkaline solution, ultrasonic treatment is further performed.

[0073] Further, the frequency of the ultrasonic treatment is 25kHz to 40kHz, for example, 26kHz to 38kHz, 28kHz to 36kHz, 29kHz to 35kHz, 30kHz to 34kHz, 32kHz to 33kHz, etc. The time of the ultrasonic treatment is 10min to 240min, for example, 20min to 220min, 50min to 200min, 80min to 180min, 100min to 160min, 120min to 150min, etc. In this way, under the conditions of the ultrasonic treatment, it is beneficial for part of the PSS in the PEDOT:PSS solution to effectively detach from PEDOT.

[0074] In some embodiments, the pH of the composite precursor solution is 8 to 12, for example, 8.5 to 11.5, 9 to 11, 9.5 to 10.5, 10 to 10.2, etc. Within the pH range, the PEDOT:PSS solution is in an alkaline atmosphere, which is conducive to the separation of PSS from PEDOT, thereby promoting the doping of olefin copolymers.

[0075] It should be noted that the alkaline solution is added to create an alkaline environment, so there is no requirement for the amount of alkaline solution added, as long as the pH of the mixed solution is alkaline after the alkaline solution is added.

[0076] In some embodiments, after the PEDOT:PSS solution is mixed with the alkaline solution, a precipitant is added, the alkaline solution is separated and removed, and a second solvent is added to obtain a composite material precursor solution.

[0077] Specifically, after adding the precipitant, a supernatant and a precipitate are obtained, wherein the supernatant mainly includes an alkaline solution, and the precipitate mainly includes PEDOT:PSS with PSS partially detached. The supernatant is removed to obtain PEDOT:PSS with PSS partially detached. It can be understood that in order to improve the purity of PEDOT:PSS with PSS partially detached, the precipitant can be used for precipitation twice or more to obtain PEDOT:PSS with PSS partially detached.

[0078] In some embodiments, the precipitant includes an alcohol solvent, and the alcohol solvent includes one or more of ethanol, butanol, and pentanol.

[0079] In some embodiments, the mass ratio of the PEDOT:PSS solution to the precipitant is 1: 4. Within the mass ratio range, it is beneficial to fully remove the alkaline solution to obtain PEDOT:PSS with PSS partially detached.

[0080] In some embodiments, the second solvent includes one or more of water and dimethyl sulfoxide.

[0081] In some embodiments, in the composite precursor solution, the concentration of PEDOT:PSS from which PSS is partially detached is 30 mg / mL to 50 mg / mL, for example, 32 mg / mL to 48 mg / mL, 34 mg / mL to 46 mg / mL, 36 mg / mL to 45 mg / mL, 38 mg / mL to 44 mg / mL, 40 mg / mL to 42 mg / mL, etc. Within the concentration range, spin coating is helpful to improve the quality of the film.

[0082] In S13:

[0083] In some embodiments, the olefin copolymer includes one or more of polyvinyl alcohol (PVA), poly(ethylene-vinyl acetate) (PEVA), polyvinyl acetate (PVAc), and styrene block copolymer.

[0084] In some embodiments, the mass ratio of the PEDOT:PSS to the olefin copolymer is 1:(0.001-0.1), for example, 1:(0.002-0.08), 1:(0.005-0.06), 1:(0.008-0.05), 1:(0.01-0.04), 1:(0.02-0.03), etc. Within the mass ratio range, the olefin copolymer can be effectively embedded between PEDOT and PSS, and combined with PEDOT to form an elastic polymer network structure.

[0085] In some embodiments, the time for mixing the composite precursor solution and the olefin copolymer is 10min to 24h, for example, 1h to 22h, 2h to 20h, 5h to 18h, 8h to 15h, 10h to 12h, etc. The temperature for mixing the composite precursor solution and the olefin copolymer is 40°C to 80°C, for example, 42°C to 78°C, 45°C to 75°C, 48°C to 72°C, 50°C to 70°C, 55°C to 60°C, etc. Under the reaction conditions, it is beneficial for the olefin copolymer to fully combine with the PEDOT and improve the hydrophobicity of the PEDOT film.

[0086] In some embodiments, the carbon atoms on the carbon-carbon double bonds of the olefin copolymer and the sulfur atoms of the PEDOT are combined by electrostatic interaction. Specifically, the structure of the composite material is shown in formula (I) (the dashed box is the olefin copolymer):

[0087]

[0088] In a second aspect, an embodiment of the present application further provides a composite material, which is prepared by the above-mentioned preparation method.

[0089] In some embodiments, the composite material includes a composite of the olefin copolymer doped with PEDOT:PSS.

[0090] In some other embodiments, the composite material may further include PEDOT:PSS from which PSS is not detached, PEDOT not bound to PSS, and PSS not bound to PEDOT.

[0091] Third, see Figure 2 The embodiment of the present application also provides a light-emitting device, including a stacked anode 10, a hole functional layer 20, a light-emitting layer 30 and a cathode 40, wherein the material of the hole functional layer 20 includes the composite material obtained by the above preparation method.

[0092] The light-emitting device provided by the present application, the material of the hole functional layer 100 includes the composite material prepared by the above-mentioned preparation method, the composite material includes PEDOT-olefin copolymer-PSS, the olefin copolymer has the advantages of low modulus, high stretchability, high interface adhesion, etc., and at the same time contains a strong conjugated structure to form a strong dipole, which is easy to combine with PEDOT. The olefin copolymer is embedded between PEDOT and PSS. Due to the large steric hindrance, the PEDOT and PSS of PEDOT:PSS can be further separated, effectively preventing PEDOT from absorbing water and swelling, and improving the hydrophobic properties of the PEDOT film, thereby realizing the formation of a tough conformal interface between the PEDOT film and the rigid electrode substrate. The light-emitting device provided by the present application has mechanical flexibility, high conductivity and long-term electrochemical stability.

[0093] In some embodiments, the materials of the anode 10 and the cathode 40 include one or more of metal, carbon material and metal oxide respectively; the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes a metal oxide electrode or a composite electrode with a metal sandwiched between doped or undoped transparent metal oxides, the material of the metal oxide electrode includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, and the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2. Here, “ / ” represents a stacked structure. For example, AZO / Ag / AZO represents a composite electrode including an AZO layer, an Ag layer and an AZO layer stacked in sequence.

[0094] In some embodiments, the material of the light-emitting layer 30 includes one or more of an organic light-emitting material and a quantum dot light-emitting material.

[0095] The organic light-emitting material includes one or more of CBP:Ir(mppy)3(4,4'-bis(N-carbazole)-1,1'-biphenyl:tris[2-(p-tolyl)pyridine iridium(III)]), TCTX:Ir(mmpy)(4,4',4"-tris(carbazole-9-yl)triphenylamine:tris[2-(p-tolyl)pyridine iridium]), diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, TADF (thermally activated delay) materials, polymers containing BN covalent bonds, HLCT (hybridized localized charge transfer excited state) materials, and Exciplex (exciplex) light-emitting materials.

[0096] The quantum dot luminescent material includes one or more of single structure quantum dots, core-shell structure quantum dots and perovskite type semiconductor materials.

[0097] The material of the single structure quantum dots, the core material of the core-shell structure quantum dots and the shell material of the core-shell structure quantum dots can be respectively selected from but not limited to one or more of the group II-VI compounds, group IV-VI compounds, group III-V compounds and group I-III-VI compounds. The II-VI group compounds include one or more of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe. The IV-VI group compounds include one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe. The III-V group compound includes one or more of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb. The I-III-VI group compound includes one or more of CuInS2, CuInSe2 and AgInS2.

[0098] As an example, the core-shell structured quantum dots include one or more of CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS and InP / ZnSe / ZnS.

[0099] The perovskite semiconductor material includes a doped or undoped inorganic perovskite semiconductor, or an organic-inorganic hybrid perovskite semiconductor. The inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion selected from Cl - Br - ,I - The general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2 + 、Eu 2+ One or more of, X is a halogen anion selected from Cl - Br - ,I - One or more of the .

[0100] In some embodiments, the hole functional layer 20 includes one or more of a hole injection layer and a hole transport layer. When the hole functional layer 20 includes a hole injection layer and a hole transport layer, the material of the hole injection layer and / or the hole transport layer is a composite material prepared by the above preparation method.

[0101] In other words, when the hole functional layer 20 includes the hole injection layer and the hole transport layer, only the material of the hole injection layer may be the composite material prepared by the above preparation method, or only the material of the hole transport layer may be the composite material prepared by the above preparation method, or both the materials of the hole injection layer and the hole transport layer may be composite materials prepared by the above preparation method.

[0102] In some embodiments, when the hole functional layer 20 includes a hole injection layer and a hole transport layer, when the hole injection layer is a composite material prepared by the above preparation method, the material of the hole transport layer includes but is not limited to 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4 ,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(carbazolyl-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent materials, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-phenylenevinylene), poly(phenylene) vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'- Di(naphthalene-1-yl)-N,N'-diphenylbenzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose and tetracyanoquinodimethane, doped graphene, undoped graphene, transition metal oxides, transition metal sulfides, transition metal tin compounds, doped or undoped zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc selenide, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, barium titanate, quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds. One or more thereof.

[0103] Correspondingly, in some embodiments, when the hole functional layer 20 includes a hole injection layer and a hole transport layer, when the hole transport layer is a composite material prepared by the above preparation method, the material of the hole injection layer includes but is not limited to 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbiphenyl Amine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(carbazolyl-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent materials, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline, polypyrrole, poly(p-phenylenevinylene), poly(ethylenevinylene) phenyl vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N' -di(naphthalene-1-yl)-N,N'-diphenylbenzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose and tetracyanoquinodimethane, doped graphene, undoped graphene, transition metal oxides, transition metal sulfides, transition metal tin compounds, doped or undoped zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc selenide, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, barium titanate, quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds. One or more of the following.

[0104] In some embodiments, the light-emitting device further includes an electronic functional layer 50. The electronic functional layer 50 includes one or more of an electron injection layer or an electron transport layer. The electronic functional layer 50 is disposed between the light-emitting layer 30 and the cathode 40. The materials of the electron injection layer and the electron transport layer independently include one or more of doped or undoped inorganic particles, quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds. The inorganic particles include one or more of zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc selenide, indium phosphide, gallium phosphide, and barium titanate, and the doped elements include one or more of indium, gallium, aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium.

[0105] In some embodiments, the thickness of the anode 10 is 80 nm to 100 nm, for example, 82 nm to 98 nm, 84 nm to 96 nm, 86 nm to 95 nm, 88 nm to 94 nm, 90 nm to 92 nm, etc.

[0106] In some embodiments, the thickness of the hole functional layer 20 is 3 nm to 70 nm, for example, 5 nm to 65 nm, 8 nm to 60 nm, 10 nm to 55 nm, 15 nm to 50 nm, 20 nm to 40 nm, etc.

[0107] Furthermore, the thickness of the hole injection layer may be 3 nm to 10 nm. The thickness of the hole transport layer may be 20 nm to 60 nm.

[0108] In some embodiments, the thickness of the light emitting layer 30 is 20 nm to 60 nm, for example, 25 nm to 58 nm, 28 nm to 55 nm, 30 nm to 50 nm, 35 nm to 48 nm, 38 nm to 40 nm, etc.

[0109] In some embodiments, the thickness of the cathode 40 is 40 nm to 80 nm, for example, 45 nm to 78 nm, 48 nm to 75 nm, 50 nm to 70 nm, 55 nm to 65 nm, 58 nm to 60 nm, etc.

[0110] In some embodiments, the thickness of the electronic functional layer 50 is 20 nm to 60 nm, for example, 25 nm to 58 nm, 28 nm to 55 nm, 30 nm to 50 nm, 35 nm to 48 nm, 38 nm to 40 nm, etc.

[0111] In some embodiments, the preparation method of the hole functional layer 20 can adopt conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction, anodization, electrolytic deposition, and coprecipitation. The physical method includes physical coating and solution method, among which the physical coating method includes: thermal evaporation coating, electron beam evaporation coating, magnetron sputtering, multi-arc ion coating, physical vapor deposition, atomic layer deposition, pulsed laser deposition, etc.; the solution method can be spin coating, printing, inkjet printing, scraping, printing, dip pulling, immersion, spraying, rolling, casting, slit coating, and strip coating.

[0112] In at least one embodiment, the preparation method of the hole functional layer 20 is a solution method. Specifically, the composite material is mixed with a solvent to obtain a hole functional dispersion liquid, and the hole functional dispersion liquid is disposed on the anode 10 to obtain the hole functional layer 20 .

[0113] In a third aspect, the present application also relates to a display device, which includes the light-emitting device.

[0114] The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptops, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, among which smart wearable devices can be, for example, smart bracelets, smart watches, virtual reality (VR) helmets, etc.

[0115] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.

[0116] Example 1

[0117] This embodiment provides a composite material, and the preparation method is as follows:

[0118] Providing 100 mL of a 50 mg / mL PEDOT:PSS solution, adding KOH to adjust the solution pH to 8, and ultrasonicating for 2 h to obtain a mixed solution;

[0119] Add 400 mL of ethanol to the mixed solution, remove the supernatant, and obtain a composite material precursor, dissolve the composite material precursor in water to obtain a 50 mg / mL intermediate solution;

[0120] 1 mg of polyvinyl alcohol was added to the intermediate solution and stirring was continued for 2 h to obtain a composite material.

[0121] Example 2

[0122] This embodiment is substantially the same as embodiment 1, except that KOH is added in this embodiment to adjust the pH value of the solution to 10.

[0123] Example 3

[0124] This embodiment is substantially the same as embodiment 1, except that KOH is added in this embodiment to adjust the pH value of the solution to 12.

[0125] Example 4

[0126] This embodiment is substantially the same as embodiment 1, except that in this embodiment, ammonia water is added to adjust the pH value of the solution to 8.

[0127] Example 5

[0128] This embodiment is substantially the same as embodiment 1, except that in this embodiment, KOH is added to adjust the pH of the solution to 8, and then ultrasonic treatment is performed for 10 minutes to obtain a mixed solution.

[0129] Example 6

[0130] This embodiment is substantially the same as embodiment 1, except that in this embodiment, KOH is added to adjust the pH of the solution to 8, and then ultrasonic treatment is performed for 4 hours to obtain a mixed solution.

[0131] Example 7

[0132] This embodiment is substantially the same as Embodiment 1, except that in this embodiment, 0.1 mg of polyvinyl alcohol is added to the mixed solution.

[0133] Example 8

[0134] This embodiment is substantially the same as embodiment 1, except that in this embodiment, 10 mg of polyvinyl alcohol is added to the intermediate solution.

[0135] Example 9

[0136] This embodiment is substantially the same as Embodiment 1, except that, in this embodiment, 1 mg of polyvinyl acetate is added to the intermediate solution.

[0137] Comparative Example 1

[0138] This comparative example is substantially the same as Example 1, except that in this comparative example, no base is added to adjust the pH, and 1 mg of polyvinyl alcohol is directly added to 100 mL of a 50 mg / mL PEDOT:PSS solution to obtain a composite material.

[0139] Comparative Example 2

[0140] The composite material of this comparative example is PEDOT:PSS.

[0141] Device Example 1

[0142] This device embodiment provides a light emitting diode, and the preparation method is as follows:

[0143] Providing an ITO glass, cleaning the ITO glass with a cleaning agent to remove stains on the surface, then ultrasonically cleaning the ITO glass with deionized water, isopropyl acetone, acetone and deionized water for 20 minutes respectively, and then drying with nitrogen to obtain an ITO anode;

[0144] The composite material of Example 1 was prepared into a solution, spin-coated at a rotation speed of 4000 rpm, and heated on a heating table at 100° C. for 30 min to obtain a 3 nm hole injection layer;

[0145] 40 μL of TFB solution was taken with a pipette and slowly dripped on the hole injection layer for spin coating at a speed of 4000 rpm for 30 seconds, followed by annealing at a temperature of 140°C for 15 minutes to obtain a 30 nm hole transport layer;

[0146] The cross-linked and cured quantum dots with CdSe as the core and ZnS as the shell were dissolved in n-octane to prepare a quantum dot solution with a concentration of 15 mg / mL; 45 μL was taken with a pipette and dropped on the hole transport layer, and spin-coated at a speed of 3500 rpm for 45 seconds, followed by annealing at a temperature of 120°C for 12 minutes to obtain a 20 nm quantum dot light-emitting layer;

[0147] A 30 mg / mL ZnO ethanol dispersion was placed on the quantum dot light-emitting layer and spin-coated at a speed of 5000 rpm for 30 seconds, followed by annealing at a temperature of 120°C for 10 minutes to obtain a 42 nm electron transport layer.

[0148] The device was placed in a vapor deposition chamber and a layer of metallic silver was thermally evaporated through a mask plate to obtain a 40nm cathode;

[0149] The device is packaged under the condition that the oxygen content and the water content are both lower than 0.1 ppm to obtain a light emitting diode.

[0150] Device Examples 2 to 9

[0151] Device Examples 2 to 9 are substantially the same as Device Example 1, except that the hole injection layers are prepared using the composite materials of Examples 2 to 9, respectively.

[0152] Device Example 10

[0153] Device Example 10 is basically the same as Device Example 1, except that in this device example, the hole injection layer and the hole transport layer are combined into a hole functional layer with a thickness of 30 nm, and the material is the composite material of Example 1.

[0154] Device Example 11

[0155] Device Example 11 is basically the same as Device Example 1, except that in this device example, the hole injection layer and the hole transport layer are combined into a hole functional layer with a thickness of 70 nm, and the material is the composite material of Example 1.

[0156] Device Example 12

[0157] Device Example 12 is basically the same as Device Example 1, except that the material of the quantum dots in this device example is a quantum dot with CdSe as the core and ZnS as the shell that has not been cross-linked and cured.

[0158] Device Comparison Examples 1 to 2

[0159] Device Comparative Examples 1-2 are substantially the same as Device Example 1, except that the composite materials of Comparative Examples 1-2 are respectively used to prepare the hole injection layers.

[0160] The roughness of the thin film of the hole injection layer in device examples 1 to 12 and device comparative examples 1 to 2 was tested by atomic force microscopy to obtain an AFM image of the hole injection thin film of device example 1. The results are shown in FIG. Figure 3 The light emitting diodes in device embodiments 1 to 12 and device comparative examples 1 to 2 were tested for luminous efficiency, turn-on voltage and leakage current, and the test results were obtained as shown in Table 1.

[0161] Among them, the detection method of luminous efficiency, turn-on voltage and leakage current is: measured by LabView controlling the efficiency test system built by QE PRO spectrometer, Keithley 2400 and Keithley 6485, and the driving current is 2mA.

[0162] Depend on Figure 3 It can be seen that the surface of the hole injection film of device embodiment 1 is flat and complete, the hole injection material is evenly distributed, and there is no obvious surface defect.

[0163] Table 1

[0164]

[0165] From Table 1, we can see that:

[0166] It can be seen from device embodiments 1 to 3 and device comparative example 2 that by treating the mixed solution with an alkaline solution to a pH of 8 to 12, the film roughness of the thin films of device embodiments 1 to 3 is below 2, which is lower than the film roughness of the thin film of device comparative example 2. The luminous efficiency of the light-emitting diodes of device embodiments 1 to 3 is much higher than that of device comparative example 2, and the turn-on voltage and leakage current are both lower than those of device comparative example 2.

[0167] It can be seen from device embodiments 1 to 3, device embodiments 5 to 6 and device comparative example 2 that by treating the mixed solution with an alkaline solution to a pH of 8 to 12, the film roughness of the thin films of device embodiments 1 to 3 is below 2, which is lower than the film roughness of the thin film of device comparative example 2. The luminous efficiency of the light-emitting diodes of device embodiments 1 to 3 and device embodiments 5 to 6 is much higher than that of device comparative example 2, and the turn-on voltage and leakage current are lower than those of device comparative example 2, indicating that adding an olefin copolymer after alkaline treatment can improve the film performance of PEDOT:PSS, thereby improving the luminescent performance of the light-emitting device;

[0168] It can be seen from device example 1, device example 4 and device comparative example 2 that whether KOH or ammonia water is used to adjust the pH to alkalinity, the film roughness is lower than that of the film of device comparative example 2, the light emitting efficiency of the light emitting diode is higher, the turn-on voltage and the leakage current are lower than those of device comparative example 2, and the effect of adjusting the pH by using KOH is better than that by using ammonia water;

[0169] It can be seen from device example 1, device examples 7 to 9 and device comparative example 2 that adding an appropriate amount of olefin copolymer, whether polyvinyl alcohol or polyvinyl acetate, has lower film roughness than the film of device comparative example 2, higher luminous efficiency, lower turn-on voltage and lower leakage current than the device comparative example 2, and the improvement effect of doping polyvinyl alcohol on PEDOT:PSS is more significant than that of doping polyvinyl acetate;

[0170] It can be seen from device example 1, device examples 10 to 12 and device comparative example 2 that changing the thickness of the hole functional layer or using uncrosslinked and cured quantum dots has little effect on the performance of the light-emitting diode. However, since alkaline PSS removal and doped olefin copolymers are used, the film roughness of device examples 1 and device examples 10 to 12 is significantly reduced, the luminous efficiency is significantly improved, and the turn-on voltage and leakage current are effectively improved relative to device comparative example 2.

[0171] It can be seen from device example 1 and device comparison examples 1 to 2 that device example 1 using alkaline dedoping reduces film roughness, improves luminous efficiency, and reduces turn-on voltage and leakage current; since device comparison example 1 is doped with olefin copolymer compared to device comparison example 2, device comparison example 1 has lower film roughness than device comparison example 2, and the performance of the light-emitting diode is slightly better.

[0172] The composite materials and preparation methods thereof, light-emitting devices, and display devices provided in the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the methods and core ideas of the present application. At the same time, for technical personnel in this field, according to the ideas of the present application, there will be changes in the specific implementation methods and application scopes. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A method for preparing a composite material, characterized in that: include: Provide PEDOT:PSS and olefin copolymers; treating the PEDOT:PSS with alkalinity to obtain a composite material precursor solution; The olefin copolymer is mixed with the composite material precursor solution to obtain the composite material.

2. The preparation method according to claim 1, characterized in that The alkaline treatment of the PEDOT:PSS comprises: The PEDOT:PSS is dissolved in a first solvent to obtain a PEDOT:PSS solution; and the PEDOT:PSS solution is mixed with an alkaline solution to obtain the composite material precursor solution.

3. The preparation method according to claim 2, characterized in that: In the PEDOT:PSS solution, the concentration of PEDOT:PSS is 30 mg / mL to 50 mg / mL; and / or The molar concentration of the alkaline solution is 0.01 mol / L to 0.2 mol / L; and / or The pH of the composite material precursor solution is 8 to 12; and / or The alkaline solution includes one or more of KOH, NaOH, LiOH, Cs(OH)2, Ba(OH)2, NH3, and tetramethylammonium hydroxide; and / or The first solvent includes one or more of water and dimethyl sulfoxide; and / or The solvent in the alkaline solution includes water.

4. The preparation method according to claim 2, characterized in that: After mixing the PEDOT:PSS solution with the alkaline solution, ultrasonic treatment is further performed; and / or After the PEDOT:PSS solution is mixed with the alkaline solution, a precipitant is added, the alkaline solution is separated and removed, and a second solvent is added to obtain a composite material precursor solution.

5. The preparation method according to claim 4, characterized in that: The frequency of the ultrasonic treatment is 25kHz to 40kHz; and / or The ultrasonic treatment time is 10min to 240min; and / or The precipitant comprises one or more of ethanol, butanol and pentanol; and / or The second solvent includes one or more of water and dimethyl sulfoxide; and / or The mass ratio of the PEDOT:PSS solution to the precipitant is 1:

4.

6. The preparation method according to claim 1, characterized in that: In the PEDOT:PSS, the mass ratio of PEDOT to PSS is 1:(8-15); and / or In the composite material precursor solution, the concentration of PEDOT:PSS is 30 mg / mL to 50 mg / mL; and / or The mass ratio of the PEDOT:PSS to the olefin copolymer is 1:(0.001-0.1); and / or The olefin copolymer includes one or more of polyvinyl alcohol, poly(ethylene-vinyl acetate), polyvinyl acetate, and styrene block copolymer; and / or The olefin copolymer and the composite material precursor solution are mixed for 10 minutes to 24 hours; and / or The temperature for mixing the olefin copolymer and the composite material precursor solution is 40° C. to 80° C.

7. A composite material, characterized in that: The composite material is prepared by the preparation method according to any one of claims 1 to 6, wherein the composite material comprises a composite of the olefin copolymer doped with PEDOT:PSS.

8. A light emitting device, characterized in that: The invention comprises a stacked anode, a hole functional layer, a light-emitting layer and a cathode, wherein the material of the hole functional layer comprises the composite material prepared by the preparation method according to any one of claims 1 to 6.

9. The light emitting device according to claim 8, characterized in that: The thickness of the anode is 80nm to 100nm; and / or The thickness of the hole functional layer is 3nm to 70nm; and / or The thickness of the light-emitting layer is 20nm to 60nm; and / or The thickness of the cathode is 40nm to 80nm; and / or The materials of the anode and the cathode independently include one or more of metal, carbon material and metal oxide; the metal includes one or more of Al, Ag, Cu, Mo, Au, Ba, Ca, Yb and Mg; the carbon material includes one or more of graphite, carbon nanotubes, graphene and carbon fiber; the metal oxide includes a metal oxide electrode or a composite electrode with a metal sandwiched between doped or undoped transparent metal oxides, the material of the metal oxide electrode includes one or more of ITO, FTO, ATO, AZO, GZO, IZO, MZO and AMO, and the composite electrode includes one or more of AZO / Ag / AZO, AZO / Al / AZO, ITO / Ag / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, ZnS / Ag / ZnS, ZnS / Al / ZnS, TiO2 / Ag / TiO2 and TiO2 / Al / TiO2; and / or The material of the light-emitting layer includes 4,4'-bis(N-carbazole)-1,1'-biphenyl: tris[2-(p-tolyl)pyridine iridium(III)], 4,4',4"-tris(carbazole-9-yl)triphenylamine: tris[2-(p-tolyl)pyridine iridium], diarylanthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, TADF materials, polymers containing BN covalent bonds, HLCT materials, Exciplex luminescent materials, CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, Cd ZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe, HgZnSTe, SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSe S, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs , GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, G aInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, InAlPSb, CuInS2, CuInSe2, AgInS2, CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZ One or more of nSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS, InP / ZnSe / ZnS, AMX3 and BMX3, where A is Cs + ion, M is a divalent metal cation selected from Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion selected from Cl - Br - ,I - One or more of; B is an organic amine cation selected from CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n ≥ 2; and / or The light-emitting device also includes an electronic functional layer arranged between the light-emitting layer and the cathode, the electronic functional layer includes one or more of an electron injection layer or an electron transport layer, the materials of the electron injection layer and the electron transport layer independently include one or more of doped or undoped inorganic particles, quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds, the inorganic particles include one or more of zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc selenide, indium phosphide, gallium phosphide, and barium titanate, and the doped elements include one or more of indium, gallium, aluminum, magnesium, lithium, manganese, yttrium, lanthanum, copper, nickel, zirconium, cerium, and gadolinium.

10. The light emitting device according to claim 8, characterized in that: The hole functional layer comprises a hole injection layer or a hole transport layer, and the material of the hole injection layer or the hole transport layer is a composite material obtained by the preparation method according to any one of claims 1 to 6; or The hole functional layer comprises a hole injection layer and a hole transport layer, one of the hole injection layer and the hole transport layer is a composite material prepared by the preparation method according to any one of claims 1 to 6, and the material of the other layer of the hole injection layer and the hole transport layer comprises a composite material prepared by the preparation method according to any one of claims 1 to 6, 4,4'-N,N'-dicarbazolyl-biphenyl, N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N'-diphenyl (4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(carbazolyl-9-yl)triphenylamine, trichloroisocyanuric acid, terbium-doped phosphate-based green luminescent materials, 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(4-butylphenyl-diphenylamine), poly[bis(4-phenyl)(4-butylphenyl)amine], polyaniline , polypyrrole, poly(p-)phenylene vinylene, poly(phenylene vinylene), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene], poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene], copper phthalocyanine, aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT, PEDOT:PSS and its derivatives, PEDOT:PSS derivatives doped with s-MoO3, poly(N-vinylcarbazole) and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, N,N'-di(naphthalene-1-yl)-N,N'-diphenylbenzidine, spiro NPB, nano-polycrystalline diamond, microcrystalline cellulose and tetracyanoquinodimethane, doped graphene, undoped graphene, transition metal oxides, transition metal sulfides, transition metal tin compounds, doped or undoped zinc oxide, barium oxide, nickel oxide, titanium oxide, tin oxide, tantalum oxide, zirconium oxide, lithium titanium oxide, zinc aluminum oxide, zinc manganese oxide, zinc tin oxide, lithium zinc oxide, indium tin oxide, cadmium sulfide, zinc sulfide, molybdenum sulfide, tungsten sulfide, copper sulfide, zinc selenide, indium phosphide, gallium phosphide, copper indium sulfide, copper gallium sulfide, barium titanate, quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds.

11. A display device, characterized in that: The light emitting device comprises the light emitting device as claimed in any one of claims 8 to 10.